Correlation between microstructure, mechanical and thermal properties of In-Bi-Sn-Ag melt spun alloys (JOURNAL OF ADVANCES IN PHYSICS, 2015)
A series of indium-bismuth-tin-silver alloys containing up to 5 wt. % silver were quenched from melt by chill-block melt-spin technique. The resultant ribbons were studied by X-ray diffraction, scanning electron microscope, energy dispersive X-ray, and deferential scanning calorimetry techniques. Structural, Mechanical and thermal correlations were discussed and reviewed for In-Bi-Sn-Ag Fields metal alloy systems. The results are interpreted in terms of the phase changes occurring in the alloy system. It is found that melting point, solidus and liquidus temperatures of the solder alloys are lowered as the Ag content is increased. With the addition of Ag, the In rich phase is finer in size, and the intermetallic compounds are more uniformly distributed.  As a result, Youngs modulus and microhardness of In-Bi-Sn are increased when Ag is added into the solder alloy. It is also , concluded that from our results, the present work relates to a melting temperature adjustable metal thermal interface material (TIM) applicable to an interface between a microelectronic packaging component and a heat dissipation device, so as to facilitate the heat dissipation of the microelectronic component.